CircDDX17 enhances coxsackievirus B3 replication through regulating miR-1248/NOTCH receptor 2 axis - Liu, Tingjun; Li, Yuhan; Chen, Shengjie; Wang, Lulu; Liu, Xiaolan; Yang, Qingru; Wang, Yan; Qiao, Xiaorong; Tong, Jing; Deng, Xintao; Shao, Shihe; Wang, Hua; et al. (Frontiers in Microbiology, 2022)
Coxsackievirus B3 (CVB3) was one of the most common pathogens to cause viral myocarditis. Circular RNAs as novel non-coding RNAs with a closed loop molecular structure have been confirmed to be involved in virus infectious diseases, but the function in CVB3 infection was not systematically studied. In this study, we identified that hsa_circ_0063331 (circDDX17) was drastically decreased after CVB3 infection by circRNA microarray. In vivo and in vitro, when cells or mice were infected with CVB3, the expression of circDDX17 was significantly reduced, as demonstrated by quantitative real-time PCR assays. Additionally, circDDX17 enhanced CVB3 replication by downregulating the expression of miR-1248 in HeLa and HL-1 cells, and miR-1248 regulated CVB3 replication through interacting with the gene coding for NOTCH Receptor 2 (NOTCH2), and NOTCH2 could up-regulate methyltransferase-like protein 3 (METTL3). Taken together, this study suggested that circDDX17 promoted CVB3 replication and regulated NOTCH2 by targeting miR-1248 as a miRNAs sponge.